KONSELING DAN SOSIALISASI POLA ASUH BAGI ORANGTUA SISWA SDN 02 SIJUK KABUPATEN BELITUNG - Suryadi, Denrich; Pangandaheng, Aldonia; Melvin, Darren; Nurqalby, Upie Fitri; Steven, Willson; Sandra, Mega (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
SDN 02 Sijuk is located in Piak Air, Sijuk Village, with 102 students who live in Sijuk District, Belitung Regency, Bangka Belitung Islands Province. Based on needs analysis, teachers at SDN 02 Sijuk need help to provide psychoeducation about parenting styles and inclusive children problems. The purpose of this PKM program is to provide psychoeducation regarding the importance of parenting parents for the growth and development of children and to find out problems with inclusive children. PKM's current target is the parents of SDN 02 Sijuk students. The 2023 Thematic KKN MBKM group that assisted SDN 02 Sijuk made observations on 11-12 March 2023 and designed two activities, namely counseling activities for parents of inclusive children at SDN 02 Sijuk who needed private counseling which took place on 20-21 March 2023 and psychoeducational activities regarding parenting patterns on April 3, 2023. Counseling activities were attended by 6 parents of students of inclusive students and students with emotional and behavior problem. By filling feedback questionnaire, parents were feeling relieved, more capable of self-introspection, more motivated, increased knowledge, and gained more support regarding the role of parents as a driving factor for inclusive children's lives. While the results of parenting socialization activities which were attended by 50 parents of students at SDN 02 Sijuk were increasing knowledge about parenting methods, attitudes and behaviors that are beneficial for the formation of children's character. These two activities were considered successful and provided the assistance needed by the school. SDN 02 Sijuk terletak di Dusun Piak Air Desa Sijuk memiliki 102 siswa yang berdomisili di Kecamatan Sijuk Kabupaten Belitung Provinsi Kepulauan Bangka Belitung. Berdasarkan analisis kebutuhan, para guru SDN 02 Sijuk membutuhkan bantuan untuk memberikan edukasi mengenai pola asuh orang tua dan masalah terhadap beberapa anak inklusi. Tujuan program PKM ini untuk memberikan psikoedukasi mengenai pentingnya pola asuh orang tua terhadap tumbuh kembang anak serta untuk mengetahui permasalahan terhadap siswa inklusi dan anak dengan masalah emosional dan perilaku. Sasaran PKM saat ini pada para orang tua siswa SDN 02 Sijuk. Kelompok MBKM KKN Tematik 2023 yang membantu SDN 02 Sijuk telah melakukan observasi pada tanggal 11-12 Maret 2023 dan merancang dua buah kegiatan yaitu kegiatan konseling bagi orang tua anak inklusi SDN 02 Sijuk yang membutuhkan konseling secara pribadi yang berlangsung pada tanggal 20-21 Maret 2023 dan kegiatan psikoedukasi mengenai pola asuh orang tua pada tanggal 03 April 2023. Kegiatan konseling diikuti oleh 6 orangtua siswa dari anak inklusi dengan umpan balik berupa pengisian kuesioner yang berisikan jawaban yaitu perasaan lega, lebih mampu introspeksi diri, lebih termotivasi, menambah pengetahuan, dan mendapatkan lebih banyak dukungan mengenai peran orang tua yang merupakan faktor pendorong bagi kehidupan anak inklusi. Sedangkan hasil kegiatan sosialisasi pola asuh yang diikuti oleh 50 orangtua siswa SDN 02 Sijuk adalah bertambahnya pengetahuan mengenai cara pola asuh, bersikap dan berperilaku yang bermanfaat bagi pembentukan karakter anak. Dua kegiatan ini dianggap berhasil dan memberikan bantuan yang dibutuhkan oleh pihak sekolah.